ADAM protease inhibitors reduce melanogenesis by regulating PMEL17 processing in human melanocytes. Issue 2 (May 2015) - Kawaguchi, Masakazu; Hozumi, Yutaka; Suzuki, Tamio
Highlights Melanin content was reduced by the treatment with ADAM protease inhibitor. The number of mature melanosomes was reduced by the treatment with ADAM protease inhibitor. ADAM protease inhibitor acted on the processing of PMEL17 as γ-secretase and BACE2-independently.